Business Ideology: A Key Driver for Scaling Up Agroecology and Sustainable Food Systems in Africa - Dagoudo, Bienvenu Akowedaho; Ssekyewa, Charles; Chisadza, Bright; Chawanda, Chrissy; Idrissou, Latifou (Journal of Techno-Social, 2024)
Agriculture in Africa is perceived by the majority as a subsistence and traditional activity, which has hindered the potential of the agricultural sector to provide opportunities for job creation, poverty reduction, environmental solutions, and economic development. However, this perception is based on stereotypes that have destroyed the transformation or revolution in African agriculture and are entrenched in collective thinking. How can we change this perception that blinds the agricultural sector to its potential and keeps the population in a subsistence mindset? Business ideology proved to be the ideal solution for introducing the new paradigm of entrepreneurial systems thinking to the agricultural sector.  This paper explores how business ideology can be used to scale up agroecology and sustainable food systems through mindset change on the African continent. The approach of applying business ideology to scale up agroecology and sustainable food systems is designed to promote business cognition and qualitative changes in innovative technology, scientific research, and investment in agricultural services sectors of various economic sectors. Business ideology reveals the powerful cognitive phenomenon that facilitates effective decision-making through metaphor as a systems-thinking tool for collective thinking to harness the agricultural sector to create agricultural enterprises and reduce poverty through agroecology and sustainable food systems. The example of the cow metaphor illustrates the interconnectedness needed to improve decision-making in a critical agricultural environment, where scholars from various disciplines have emphasized the importance of promoting a systems-thinking mindset.